Binder composition, electrode slurry, electrode pole piece and sodium ion battery

By using a binder composition of fluoropolymer and a polymer with side chain hydroxyl/acid group-containing polymer in the positive electrode slurry of sodium ion battery, combined with the crosslinking reaction of the curing agent, the problems of poor slurry fluidity and gel phenomenon are solved, significantly improving the peel strength of the electrode sheet and reducing the resistivity.

CN119890307APending Publication Date: 2025-04-25RUIGU NEW ENERGY (SHANGHAI) MATERIAL TECH CO LTD

Patent Information

Application Number
CN202311820315.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The positive electrode slurry of sodium ion battery often has poor fluidity and gel phenomena during homogenization, and the peel strength and high resistivity after preparation into a electrode sheet.

Method used

Using a binder composition, including a first binder (fluoropolymer, such as polyvinylidene fluoride) and a second binder (polymer with side chains containing hydroxyl and/or acid groups), and a curing agent (such as amino resin, melamine), a crosslinking network is formed through a crosslinking reaction to improve the peel strength and conductivity of the electrode sheet.

Benefits of technology

The uniformity and fluidity of the positive electrode slurry are significantly improved, the gel phenomenon is avoided, and the peel strength of the electrode sheet is greatly improved and the resistivity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004633797950000071
    Figure BDA0004633797950000071
  • Figure BDA0004633797950000102
    Figure BDA0004633797950000102
Patent Text Reader

Abstract

The invention discloses a binder composition, an electrode paste, an electrode pole piece and a sodium ion battery, the binder composition comprises a first binder, a second binder and a curing agent, the first binder is a fluorine-containing polymer, the second binder is a polymer with a side chain containing hydroxyl and / or an acidic group, and the curing agent is a polymer with a side chain containing hydroxyl and / or an acidic group. And the curing agent and the second binder are subjected to a cross-linking reaction at 80-150 DEG C. The adhesive composition provided by the invention is used for the electrode slurry, the uniformity of the slurry is improved, the gel condition is avoided, and when the slurry is used for preparing an electrode plate, the peel strength of the electrode plate can be greatly improved, and the resistivity of the electrode plate can be greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to binder compositions, electrode pastes, electrode sheets, and sodium-ion batteries. Background Technology

[0002] Due to the uneven global distribution and volatile prices of lithium resources, the vigorous development of new energy electric vehicles and large-scale energy storage systems faces supply chain instability. Meanwhile, rising prices of raw materials for lithium-ion batteries have further accelerated the development of low-cost, high-performance rechargeable batteries. Sodium-ion batteries, invented in the 1980s, offer several advantages. Firstly, sodium is more abundant in the Earth's crust than lithium by three orders of magnitude and is widely available, allowing for independent development. Secondly, sodium-ion batteries have a significant cost advantage. Furthermore, sodium ions have a smaller Stokes diameter than lithium ions and exhibit excellent low-temperature performance, making them a low-cost, high-performance rechargeable battery suitable for widespread application in electric vehicles and energy storage. Their electrochemical reaction mechanism during charging and discharging is remarkably similar to that of lithium-ion batteries, and existing lithium-ion battery manufacturing equipment can fully meet the production requirements of sodium-ion batteries, thus demonstrating enormous application potential and prospects.

[0003] Similar to lithium-ion batteries, sodium-ion batteries are mainly composed of a positive electrode, a negative electrode, a separator, an electrolyte, and a casing for encapsulating the battery. As one of the most important main materials, the positive electrode material has an excess of sodium salt added during the production process. After high-temperature sintering, the residual Na2O reacts with H2O and CO2 in the air to form NaOH and Na2CO3, making the material alkaline. Its pH is generally >13, which is much more alkaline than that of lithium-ion battery positive electrode materials.

[0004] During the homogenization process, NaOH generated on the material surface and Na2CO3 attack the binder polyvinylidene fluoride (PVDF) in the system, undergoing an elimination reaction to form double bonds accompanied by H2O generation. These double bonds are unstable in air and readily react with oxygen to form peroxides, which then decompose to produce oxygen free radicals. These free radicals then self-couple, leading to PVDF cross-linking and causing the slurry to become gel-like, affecting its performance. Completely removing residual alkali from the material during actual production, transportation, and storage is extremely difficult. If a humidity environment below 10% cannot be maintained during electrode production, rapid gelation during slurry preparation not only affects coating efficiency and uniformity but also the electrochemical performance of the electrode. Switching to other binders can avoid gelation, but the electrode's processing performance, electrochemical performance, and cycle performance will be significantly and unpredictably affected. This is why PVDF has remained a popular binder for so long in the battery industry.

[0005] Chinese patent application CN115275205A addresses the difficulty of processing positive electrode slurry gel by adding organic weak acids and sodium-ion-containing additives. Chinese patent application CN115084522A uses carboxylic acid esters, organic acids, and unsaturated fatty acids to form additives to reduce the alkalinity of the slurry and improve the material dispersion performance. However, the introduction of additional substances will reduce the bonding performance of PVDF and affect the resistivity of sodium-ion battery electrodes.

[0006] Chinese patent application CN116111091A uses a compound adhesive of polyvinylidene fluoride, polymethacrylic acid and polymethyl vinyl ether copolymaleic acid as a binder to solve the gelation problem. However, the introduction of polymethacrylic acid and polymethyl vinyl ether copolymaleic acid will affect the electrode processing performance, and there are problems of poor electrode peel strength and low conductivity in the process of preparing the positive electrode slurry into an electrode. Summary of the Invention

[0007] To overcome the problems of poor flowability and gelation often occurring during the homogenization process of sodium-ion battery positive electrode slurry preparation, as well as poor peel strength and high resistivity of the electrode sheets during preparation, this invention provides a binder composition, electrode slurry, electrode sheets, and a sodium-ion battery. The binder composition provided by this invention, used in the electrode slurry, improves the uniformity of the slurry, avoids gelation, and significantly improves the peel strength and reduces the resistivity of the electrode sheets when prepared using this slurry.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides an adhesive composition comprising a first adhesive, a second adhesive, and a curing agent, wherein the first adhesive is a fluoropolymer, the second adhesive is a polymer with hydroxyl and / or acidic groups in its side chains, and the curing agent undergoes a crosslinking reaction with the second adhesive at 80-150°C.

[0010] In this invention, the first adhesive may be a fluorinated polyolefin, preferably polyvinylidene fluoride.

[0011] In some preferred embodiments, the first adhesive is polyvinylidene fluoride.

[0012] The molecular weight of the polyvinylidene fluoride can be 55w-120w, for example 110w.

[0013] In this invention, the second binder is a polymer with hydroxyl and / or acidic groups in the side chain, which can neutralize the residual alkali on the surface of the active material, inhibit the gelation of the positive electrode slurry, and help disperse the positive electrode active material, ultimately obtaining a uniform positive electrode slurry with good flowability, especially a sodium ion positive electrode slurry.

[0014] In this invention, the acidic group in the second adhesive may be a carboxyl group.

[0015] In some preferred embodiments, the second adhesive is an acrylic polymer, preferably an acrylic copolymer.

[0016] The molecular weight of the acrylic copolymer can be 1w-12w.

[0017] In this invention, the curing agent can undergo a cross-linking reaction with the second binder at 80-150°C. Therefore, when the binder composition is used to prepare electrode sheets, the curing agent can undergo a cross-linking reaction with the second binder during the electrode drying process to form a cross-linked network, thereby improving the peel strength and conductivity of the electrode sheet.

[0018] In some preferred embodiments, the curing agent is one or more of isocyanate, amino resin and epoxy resin, preferably amino resin, and more preferably melamine.

[0019] In some preferred embodiments, based on the total mass of the adhesive composition, the adhesive composition comprises, by mass percentage, 50%-98% of the first adhesive, 1.5%-40% of the second adhesive, and 0.5%-10% of the curing agent.

[0020] The content of the first adhesive is preferably 70% to 80%, for example 78%.

[0021] The content of the second adhesive is preferably 10% to 30%, for example 20%.

[0022] The curing agent content is preferably 0.5% to 5%, for example 2%.

[0023] In some preferred embodiments, the adhesive composition includes polyvinylidene fluoride, acrylic copolymer, and melamine.

[0024] In some more preferred embodiments, the adhesive composition comprises 70% to 80% polyvinylidene fluoride, 10% to 30% acrylic acid copolymer, and 0.5% to 5% melamine.

[0025] In some specific embodiments, the adhesive composition comprises 78% polyvinylidene fluoride, 20% acrylic copolymer and 2% melamine.

[0026] Secondly, the present invention provides an electrode paste comprising the following components:

[0027] Electrode material 80%-99.8%,

[0028] Conductive agent 0.1%-10%,

[0029] Adhesive composition 0.1%-10%,

[0030] The remainder is organic solvent;

[0031] Wherein, the binder composition is the binder composition as described above; the percentage is the mass percentage of each component in the electrode paste.

[0032] In this invention, the content of the electrode material is preferably 94%-97%, for example 95%.

[0033] In this invention, the content of the conductive agent is preferably 1%-2%.

[0034] In this invention, the content of the adhesive composition is preferably 2%-4%, for example 3%.

[0035] In some specific embodiments, the electrode paste comprises a composition of 95% electrode material, 2% conductive agent, and 3% binder.

[0036] In this invention, the electrode material is preferably a positive electrode material, which can be selected from one or more of sodium nickel iron manganese oxide, sodium copper iron manganese oxide, sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium vanadium pyrophosphate, Prussian white and Prussian blue, such as sodium nickel iron manganese oxide, sodium vanadium phosphate or Prussian blue.

[0037] In this invention, the conductive agent may be selected from one or more of acetylene black, carbon black, carbon nanotubes and graphene, such as carbon black.

[0038] In this invention, the organic solvent can be a conventional choice in the art, such as N-methylpyrrolidone (NMP).

[0039] In some specific embodiments, the electrode paste comprises 94%-97% sodium nickel manganese oxide, 1%-2% carbon black, and 2%-4% of the binder composition.

[0040] In some specific embodiments, the electrode paste comprises 94%-97% sodium vanadium phosphate, 1%-2% carbon black, and 2%-4% of the binder composition.

[0041] In some specific embodiments, the electrode paste comprises 94%-97% Prussian blue, 1%-2% carbon black, and 2%-4% of the binder composition.

[0042] In some specific embodiments, the electrode paste comprises 95% sodium nickel manganese oxide, 2% carbon black, and 3% of the binder composition.

[0043] In some specific embodiments, the electrode paste comprises 95% sodium vanadium phosphate, 2% carbon black, and 3% of the binder composition.

[0044] In some specific embodiments, the electrode paste comprises 95% Prussian blue, 2% carbon black, and 3% of the binder composition.

[0045] In this invention, the solid content of the electrode slurry can be 40%-80%, for example 68%, 62% or 51%.

[0046] The solid content is the mass percentage of the electrode material, conductive agent, and binder composition in the total electrode slurry.

[0047] In this invention, the viscosity of the electrode slurry can be 3000-10000 mPa·s, for example 7000 mPa·s.

[0048] In some embodiments of the present invention, the preparation method of the electrode slurry includes the following steps: adding the electrode material, the conductive agent and the binder composition to the organic solvent, mixing and homogenizing.

[0049] The mixing method may be stirring.

[0050] The homogenization can be performed using conventional homogenization equipment in the art, such as a homogenization tank.

[0051] Thirdly, the present invention provides an electrode sheet comprising an electrode current collector and an electrode material layer disposed on at least one surface of the electrode current collector, wherein the electrode material layer is prepared using the aforementioned electrode slurry.

[0052] In this invention, the electrode sheet is preferably a positive electrode sheet.

[0053] In some embodiments of the present invention, the method for preparing the electrode sheet includes the following steps:

[0054] The electrode slurry is coated onto at least one surface of the electrode current collector, dried, and pressed to form an electrode material layer.

[0055] In this invention, the electrode current collector can be any material conventional in the art. When the electrode current collector is a positive current collector, it is, for example, an aluminum foil.

[0056] Furthermore, the thickness of the aluminum foil is a conventional choice in the art, preferably 10-20 μm, for example 18 μm.

[0057] In this invention, the drying operation is conventional in the art, such as oven drying.

[0058] Preferably, the drying temperature is 80-150°C, for example 120°C.

[0059] Preferably, the drying time is 4-30 minutes.

[0060] In this invention, the pressing method can be conventional in the art, such as roller pressing.

[0061] Fourthly, the present invention provides a sodium-ion battery comprising the electrode plates as described above.

[0062] On the basis of conforming to the common sense in this field, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0063] The reagents and raw materials used in this invention are all commercially available.

[0064] The positive and progressive effects of this invention are as follows:

[0065] (1) This invention uses a polymer containing acidic groups (such as a large number of carboxyl groups (-COOH)) and / or hydroxyl (-OH) functional groups as a second binder, which is used in conjunction with the first binder, a fluoropolymer, to facilitate the dispersion of electrode materials and improve the uniformity of the slurry. The large number of acidic groups and / or hydroxyl (-OH) functional groups in the second binder can neutralize the residual alkali on the surface of the electrode material, avoiding severe gelation of the slurry when using the fluoropolymer alone, and reducing the difficulty of coating. At the same time, this invention adds a curing agent to the binder composition. During the electrode drying process, the curing agent can react chemically with the second binder to form chemical bonds and build a cross-linked network, which greatly improves the peel strength of the electrode and can further reduce the resistivity of the electrode.

[0066] (2) The binder composition of the present invention is applicable to electrode materials (especially positive electrode materials) in various sodium-ion battery fields, and has good compatibility and convenience, and has the prospect of large-scale commercial application. Detailed Implementation

[0067] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0068] The main reagents and equipment used in the following examples are shown in Tables 1 and 2, respectively:

[0069] Table 1

[0070]

[0071] Table 2

[0072] equipment Manufacturer or model Universal testing machine Shimadzu Enterprise Management China Co., Ltd. Four-probe electrode resistivity meter Guangzhou Four-Probe Technology Co., Ltd.

[0073] Example 1

[0074] This embodiment provides a method for preparing sodium-ion battery electrode slurry and electrode sheets. The specific operation steps are described below:

[0075] Sodium nickel iron manganese oxide, conductive agent, and binder composition were weighed according to a mass ratio of 95:2:3; wherein the conductive agent is carbon black, and the binder composition is a combination of polyvinylidene fluoride, acrylic acid copolymer, and melamine, and the mass ratio of each component of the binder composition is 78:20:2; the total weight of the powder is 200g, which is placed in a homogenizing tank, and an appropriate amount of NMP is added and stirred thoroughly to obtain a sodium-ion battery positive electrode slurry with a solid content of 68% and a viscosity close to 7000mPa·s.

[0076] The obtained electrode slurry was coated on an 18μm aluminum foil and dried in a forced-air oven at 120℃ for 30 minutes to fully remove residual organic solvents. The resulting positive electrode sheet for sodium-ion batteries was obtained by rolling.

[0077] Example 2

[0078] This embodiment provides a method for preparing sodium-ion battery electrode slurry and electrode sheets. The specific operation steps are described below:

[0079] Sodium vanadium phosphate, conductive agent, and binder composition were weighed according to a mass ratio of 95:2:3; wherein the conductive agent is carbon black, and the binder composition is a combination of polyvinylidene fluoride, acrylic acid copolymer, and melamine, and the mass ratio of each component of the binder composition is 78:20:2; the total weight of the powder is 200g, which is placed in a homogenizing tank, and an appropriate amount of NMP is added and stirred thoroughly to obtain a sodium-ion battery positive electrode slurry with a solid content of 62% and a viscosity close to 7000mPa·s.

[0080] The obtained electrode slurry was coated on an 18μm aluminum foil and dried in a forced-air oven at 120℃ for 30 minutes to fully remove residual organic solvents. The resulting positive electrode sheet for sodium-ion batteries was obtained by rolling.

[0081] Example 3

[0082] This embodiment provides a method for preparing sodium-ion battery electrode slurry and electrode sheets. The specific operation steps are described below:

[0083] Prussian blue, conductive agent, and binder composition were weighed according to a mass ratio of 95:2:3; wherein the conductive agent is carbon black, and the binder composition is a combination of polyvinylidene fluoride, acrylic acid copolymer, and melamine, with the mass ratio of each component of the binder composition being 78:20:2; the total weight of the powder was 200g, placed in a homogenizing tank, and an appropriate amount of NMP was added and stirred thoroughly to obtain a sodium-ion battery positive electrode slurry with a solid content of 51% and a viscosity close to 7000mPa·s.

[0084] The obtained electrode slurry was coated on an 18μm aluminum foil and dried in a forced-air oven at 120℃ for 30 minutes to fully remove residual organic solvents. The resulting positive electrode sheet for sodium-ion batteries was obtained by rolling.

[0085] Comparative Example 1

[0086] The sodium-ion battery positive electrode slurry and positive electrode sheet differ from those in Example 1 only in that the binder composition is a PVDF and acrylic copolymer composition, and does not contain the curing agent melamine.

[0087] Comparative Example 2

[0088] The sodium-ion battery positive electrode slurry and positive electrode sheet differ from those in Example 1 only in that the binder composition is an acrylic copolymer + curing agent composition, which does not contain PVDF.

[0089] Comparative Example 3

[0090] The sodium-ion battery positive electrode slurry and positive electrode sheet differ from those in Example 1 only in that the binder composition contains only PVDF and does not contain acrylic copolymer or curing agent.

[0091] Comparative Example 4

[0092] The difference between the sodium-ion battery positive electrode slurry and positive electrode sheet and those in Example 1 is that the mass ratio of PVDF, acrylic copolymer, and curing agent is 89:10:1.

[0093] Comparative Example 5

[0094] The difference between the sodium-ion battery positive electrode slurry and positive electrode sheet and those in Example 1 is that the mass ratio of PVDF, acrylic copolymer, and curing agent is 56:40:4.

[0095] Comparative Example 6

[0096] The sodium-ion battery positive electrode slurry and positive electrode sheet differ from those in Example 1 only in that the binder composition has a PVDF to curing agent mass ratio of 98:2 and does not contain acrylic copolymer.

[0097] Effect Example

[0098] (1) Slurry fineness

[0099] The sodium-ion battery cathode slurry prepared in the above examples and comparative examples was used to test the fineness of the slurry.

[0100] The fineness of the slurry was tested using a scraper fineness gauge. The slurry was dripped onto the scraper fineness gauge, and the scraper was used to scrape the slurry downwards to read the reading corresponding to the fault.

[0101] (2) Slurry gelation test

[0102] Take the sodium-ion battery positive electrode slurry prepared in the above examples and comparative examples, put it into a 250mL beaker, let it stand at room temperature with 30% relative humidity, and record the time when the slurry gels.

[0103] (3) Electrode state

[0104] Observe the thickness uniformity and cracking of the sodium-ion battery positive electrode sheets prepared in the above examples and comparative examples, and record the state of the electrode sheets.

[0105] (4) Peel strength

[0106] The sodium-ion battery positive electrode sheets prepared in the above embodiments and comparative examples are cut into rectangular strips of 16cm×20mm using a cutting machine. A smooth base plate is prepared, and 5-6cm of double-sided tape is attached to the smooth base plate. The other side of the electrode sheet to be tested is in close contact with the double-sided tape, and a universal testing machine is used for 180° testing.

[0107] (5) Resistivity

[0108] The sodium-ion battery positive electrode slurry prepared in the above embodiments and comparative examples was coated onto PET sheets, dried, cut into circles by a cutting machine, and tested using a four-probe electrode resistivity meter.

[0109] Related sodium-ion battery cathode slurry fineness, gel time, electrode condition, peel strength, and resistance.

[0110] See Table 3 below for rate data.

[0111] Table 3

[0112]

[0113] Comparative data from Examples 1, 2, and 3 in Table 3 show that the binder composition in the sodium-ion battery positive electrode slurry obtained in this invention uses an acrylic copolymer containing a large number of carboxyl (-COOH) and hydroxyl (-OH) groups, which can effectively improve the uniformity of the slurry, prolong the gel time of the slurry, and has good compatibility with sodium battery positive electrode materials. Examples 1, Comparative Examples 1 and 2 show that the lack of PVDF or curing agent will cause the electrode to crack. Examples 1, Comparative Examples 4 and 5 show that too little acrylic copolymer content will weaken the anti-gel time of the slurry, while too much acrylic copolymer content will reduce the bonding strength of the electrode. Data from Examples 1, Comparative Examples 3 and 6 show that compared with polyvinylidene fluoride (PVDF), the sodium-ion battery positive electrode binder composition, in addition to prolonging the gel time of the slurry and improving the uniformity of the slurry, can also improve the peel strength and conductivity of the electrode; polyvinylidene fluoride (PVDF) does not produce a synergistic effect with the curing agent, and the above effects are not achieved when only the two are present.

[0114] Finally, it should be noted that the specific embodiments described herein are merely illustrative of the spirit of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.

Claims

1. A binder composition, characterized in that: The invention comprises a first binder, a second binder and a curing agent, wherein the first binder is a fluorine-containing polymer, the second binder is a polymer with a side chain containing hydroxyl groups and / or acidic groups, and the curing agent undergoes a cross-linking reaction with the second binder at 80-150°C.

2. The adhesive composition according to claim 1, characterized in that The first binder is a fluorine-containing polyolefin, preferably polyvinylidene fluoride, and the molecular weight of the polyvinylidene fluoride is preferably 55w-120w, such as 110w.

3. The adhesive composition according to claim 1, characterized in that The acidic group in the second binder is a carboxyl group. Preferably, the second binder is an acrylic polymer, more preferably an acrylic copolymer. The molecular weight of the acrylic copolymer is preferably 1w-12w.

4. The adhesive composition according to claim 1, characterized in that The curing agent is one or more of isocyanate, amino resin and epoxy resin, preferably amino resin, more preferably melamine.

5. The adhesive composition according to claim 1, characterized in that In terms of mass percentage, the adhesive composition comprises 50%-98% of the first adhesive, 1.5%-40% of the second adhesive and 0.5%-10% of the curing agent. Preferably, the adhesive composition comprises 78% polyvinylidene fluoride, 20% acrylic copolymer and 2% melamine.

6. An electrode slurry, characterized in that: The components include: Electrode material 80%-99.8%, Conductive agent 0.1%-10%, Binder composition 0.1%-10%, The remaining amount of organic solvent, The adhesive composition is the adhesive composition according to any one of claims 1 to 5.

7. The electrode slurry according to claim 6, characterized in that Satisfy one or more of the following conditions af: a. The content of the electrode material is 94%-97%, for example 95%; b. The content of the conductive agent is 1%-2%; c. The content of the binder composition is 2%-4%, for example 3%; d. The electrode material is a positive electrode material selected from one or more of sodium nickel iron manganate, sodium copper iron manganate, sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium vanadium pyrophosphate, Prussian white and Prussian blue, such as sodium nickel iron manganate, sodium vanadium phosphate or Prussian blue; e. The conductive agent is selected from one or more of acetylene black, carbon black, carbon nanotubes and graphene, such as carbon black; f. The organic solvent is N-methylpyrrolidone.

8. The electrode slurry according to claim 6, characterized in that The solid content of the electrode slurry is 40%-80%, for example 68%, 62% or 51%; And / or, the viscosity of the electrode slurry is 3000-10000 mPa·s, for example 7000 mPa·s.

9. An electrode plate, characterized in that: It comprises an electrode current collector and an electrode material layer arranged on at least one surface of the electrode current collector, wherein the electrode material layer is prepared by using the electrode slurry as described in any one of claims 6 to 8; and the electrode plate is preferably a positive electrode plate.

10. A sodium ion battery, characterized in that: Including the electrode plate as described in claim 9.

Citation Information

Patent Citations

  • Anode slurry additive for sodium-ion battery

    CN115084522A

  • Sodium-ion battery positive electrode slurry and preparation method and application thereof

    CN115275205A

  • Binder composition, sodium ion battery positive electrode slurry and sodium ion battery

    CN116111091A

Cited By

  • Binder composition of sodium ion battery positive electrode, positive plate and sodium ion battery

    CN121450259A